Evaluation of the Anti-Cancer Effect of TRAF2 and NCK In teracting Protein Kinase (TNIK) Inhibition in Breast Cancer Cells - Kaan Furkan Hamarat; Gamze Güney Eskiler; Selin Zeynep Özçelik; Süleyman Kaleli (Sakarya Tıp Dergisi)
Objective: This study aimed to evaluate the anticancer effect of NCB-0846, a TNIK inhibitor, in MCF-7 cells and to assess its impact on the expression levels of NF-κB and TNFA at the gene level. Materials and Methods: The MCF-7 cell line was cultured at 37°C in a 5% CO2 atmosphere using Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and antibiotics (50 IU/mL penicillin and 50 mg/mL streptomycin). Cell viability was analyzed using the CCK-8 assay to determine the cytotoxic effect of NCB- 0846. Acridine Orange/Propidium Iodide (AO/PI) staining was performed to evaluate the effect of NCB-0846 on cellular morphology in the MCF-7 cell line. Total RNA was isolated from cells treated with NCB-0846. Data analysis was performed using the SPSS 22.0 statistical program. Results: The data indicated that NCB-0846 significantly decreased the viability rates of MCF-7 cells in a dose-dependent manner (1-3 μM, p<0.01). RT-PCR analysis revealed that the expression level of NFKB1 increased 5.4-fold compared to the control group in MCF-7 cells treated with NCB-0846 at the effective dose and duration (p<0.01). In contrast, the expression level of TNFA decreased to 0.4-fold compared to the control group (p<0.01). Conclusion: The results demonstrate that NCB-0846 induces changes in the mRNA levels of the NFKB1 and TNFA genes, which are associated with inflammatory signalling pathways in MCF-7 cells. However, further molecular analyses are necessary to clarify the effect of NCB-0846 on inflammation in breast cancer and other cancer types.